190k views
4 votes
HELP ASAP!!!!!!!!!!!!!!!!!!!!!!!!

HELP ASAP!!!!!!!!!!!!!!!!!!!!!!!!-example-1
User Azjezz
by
5.5k points

2 Answers

2 votes

Answer:

B: x^2-9/x^2-4

Explanation:

numerator:

(x+3)(x-3) = x^2-3x+3x-9 = x^2 - 9

denominator:

(x+2)(x-2) = x^2-2x+2x-4 = x^2 - 4

final answer:

x^2-9 /x^2-4

User Yodhevauhe
by
5.7k points
3 votes

Answer:

B

Explanation:

X^2 3*3=9

X^2 2*2=4

Hope this helps. I've done something like this before. (: Good luck

User Mevets
by
5.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.